1993
DOI: 10.1351/pac199365010047
|View full text |Cite
|
Sign up to set email alerts
|

Cyanoalkynes: Magic wands for the preparation of novel aromatic compounds

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…I have always remained very thankful to both of them, as I have been to the late Karsten Krohn, who was my mentor at Paderborn in 1995. Back in 1989 already, Henning Hopf had told me that his group had made a doubly benzoannelated triquinacene,[160] but it was only in 2012 that I received an e‐mail telling me that Georgios Markopoulos, one of his doctoral students, had possibly obtained a hydrocarbon that resembles the parent tribenzotriquinacene 57 (R = H). Upon treatment of a mixture of the stereoisomeric 2‐benzylidene‐1,3‐diphenylpropane‐1,3‐diols ( 67 ) with acid catalysts, they had obtained very high‐melting‐point crystals that had a remarkably simple 1 H NMR spectrum.…”
Section: The Tribenzotriquinacene Storymentioning
confidence: 99%
“…I have always remained very thankful to both of them, as I have been to the late Karsten Krohn, who was my mentor at Paderborn in 1995. Back in 1989 already, Henning Hopf had told me that his group had made a doubly benzoannelated triquinacene,[160] but it was only in 2012 that I received an e‐mail telling me that Georgios Markopoulos, one of his doctoral students, had possibly obtained a hydrocarbon that resembles the parent tribenzotriquinacene 57 (R = H). Upon treatment of a mixture of the stereoisomeric 2‐benzylidene‐1,3‐diphenylpropane‐1,3‐diols ( 67 ) with acid catalysts, they had obtained very high‐melting‐point crystals that had a remarkably simple 1 H NMR spectrum.…”
Section: The Tribenzotriquinacene Storymentioning
confidence: 99%
“…Chemoselective ruthenium-catalyzed cycloadditions leading to cyanoarenes (50) and 2-alkynylpyridines (51). which clearly indicated that the neutral Ru-complex is responsible for the formation of cyanobenzenes, whereas, cationic Rucomplex generated in-situ plays a crucial role for the 2alkynylpyridines formation.…”
Section: Scheme 25mentioning
confidence: 97%
“…They assumed that cyanoacetylene dimerizes to 1,2-dicyanocyclo butadiene and synthesized various novel aromatic and heteroaromatic compounds by trapping it with various aromatic and heteroaromatic dienes (Scheme 27). [51] In 1968, Sasaki and co-worker described the 1,3-dipolar cycloaddition between cyanoacetylene and aromatic nitrile oxide. [52] In the following year, they documented the synthesis of cyclobutene ring (54) by the reaction of diethyl-aminocyanoacetylene (53) with hydrogen chloride gas (Scheme 28).…”
Section: Transition Metal-free Synthesis Of Various Carbo-/heterocyclmentioning
confidence: 99%
“…Reduction at the vinylidene alpha carbon C(1), which is consistent with the composition of the LUMO, is more in keeping with the spectroelectrochemical results. vinylidenes to alkynes at half-sandwich ruthenium and iron centres [37], future work from this group will address the potential to use a combination of these chemistries to provide a simple ruthenium-catalysed route to cyanoalkynes [108] from [9]BF 4 and terminal alkynes and to make these useful reagents readily available.…”
Section: Electronic Structure Calculations and Spectroelectrochemistrymentioning
confidence: 99%